Blue tights - Williams-Garcia, Rita. (New York : Lodestar Books, 1988)
Growing up in a city neighborhood, fifteen-year-old Joyce, unsure of herself and not quite comfortable with her maturing body, tries to find a place to belong and a way to express herself through dance.
Keywords: African Americans -- Fiction; Self-confidence -- Fiction; Dance -- Fiction; City and town life -- Fiction